Honor bound - Caine, Rachel; Aguirre, Ann (Caine, Rachel. Honors, 2019)
Savvy criminal turned skilled Leviathan pilot Zara Cole finds new friends and clashes with bitter enemies in the second book of this action-packed series from New York Times bestselling authors Rachel Caine and Ann Aguirre that's perfect for fans of The 100 and The Fifth Wave. Zara Cole was a thief back on Earth, but she's been recently upgraded to intergalactic fugitive. On the run after a bloody battle in a covert war that she never expected to be fighting, Zara, her co-pilot Beatriz, and their Leviathan ship Nadim barely escaped the carnage with their lives. Now Zara and her crew of Honors need a safe haven, far from the creatures who want to annihilate them. But they'll have to settle for the Sliver: a wild, dangerous warren of alien criminals. The secrets of the Sliver may have the power to turn the tide of the war they left behind--but in the wrong direction. Soon Zara will have to make a choice: run from the ultimate evil--or stand and fight.